Evaluation of Amikacin Pharmacokinetics in Critically Ill Patients with Intra-abdominal Sepsis - Bita Shahrami; Farhad Najmeddin; Mohammad Reza Rouini; Atabak Najafi; Kourosh Sadeghi; Shahideh Amini; Seyedeh Sana Khezrnia; Hamid Reza Sharifnia; Mojtaba Mojtahedzadeh (Tabriz University of Medical Sciences, 2020)
Purpose: Although the current widespread use of amikacin is in intra-abdominal sepsis treatment, its pharmacokinetic changes in the present setting are not yet well known. This study was aimed to evaluate the amikacin pharmacokinetic profile in critically ill patients with intraabdominal sepsis compared to pneumosepsis. Methods: Adult septic patients received amikacin therapy were studied. Patients with intraabdominal sepsis were enrolled in group 1 (n=16), and patients with pneumosepsis were enrolled in group 2 (n=13). The amikacin serum concentrations were evaluated in the first, second, fourth and sixth hours after initiating 30-minute infusion. The pharmacokinetic parameters were calculated for each patient. Results: There was no significant difference in the volume of distribution between the two groups (0.33±0.08 vs. 0.28±0.10 L/kg, P=0.193). The amikacin clearance was significantly lower in group 1 compared to group 2 (58.5±21.7 vs. 83.9±37.0 mL/min, P=0.029). There was no significant correlation between amikacin clearance and creatinine clearance estimated by Cockcroft-Gault formula in all patients (P=0.206). The half-life was significantly longer in group 1 compared to group 2 (5.3±2.8 vs. 3.4±3.2 hours, P=0.015). Conclusion: Pathophysiologic changes following intra-abdominal sepsis can affect amikacin pharmacokinetics behavior. The clearance and half-life may change, but the alteration of the volume of distribution is not significantly different in comparison with pneumosepsis. Further studies are required to evaluate the pharmacokinetic variables of amikacin in critically ill patients with intra-abdominal sepsis.